Akumulasi dan Toksisitas Effluen yang Mengandung Kromium pada Ikan Gupi (Poecilia reticulata) - Djohan, Djohan (Universitas Atma Jaya Yogyakarta, 2009)
Accumulation and toxicityofchromium in leather-tannery effluent on guppies were investigated. An acute (96 hour) statictoxicitytestingusing 5 serialdilution of theeffluentwas conducted. Each serial dilution consisted of 3 replicates, with eachreplicate contained 5litres of diluted effluent and 10 fish. Theeffluent was diluted 0.2%to 3.2%(v/v).Theconcentrations of chromium in thedilutedeffluent and fishrange from 0.9 - 9.1 µg.mL-1and 1.4 - 58.9 µg.g-1w.w, respectively. Bioconcentration factors inthisstudy vary from 1 to 39, with a median value of 6.2. The values of LC50and ILC50are 4.2 µg.mL-1and 56 µg.g-1w.w, respectively. The results show that chromiumaccumulates in guppy and causesacute toxicity. A comparison withthe concentrations of chromium in effluent, water, and fish from otherstudies was also reported.